Synthesis and characterization of a H-bonded charge-transfer complex formed between 1,10-phenanthroline monohydrate with some ?-acceptors in different solvents - Ishrat, Urfi; Abdulsatar Abduljabbar Rzokee (Journal of Science and Technology, 2025)
The charge-transfer complexes of the 1,10-phenanthroline monohydrate with m-dinitrobenzene, p-hydroxybenzoic acid, 3,5-dinitrosalicylic acid, and 3,5-dinitrobenzoic acid have been prepared and characterised by using different techniques like the 1H NMR, TGA-DTA, XRD, and FT-IR Fluorescence and Conductivity data indicate a charge-transfer interaction and as far as complexes are concerned, this interaction is associated with a H bonding and the transfer of H+ from the acceptor to the donor molecules. The FT-IR and 1H NMR spectroscopic data also indicated a charge-transfer interaction associated with a proton migration from the acceptor to the donor followed by intermolecular H bonding.